PENYULUHAN KESEHATAN TENTANG PERAWATAN PAYUDARA DI PUSKESMAS LAMTEUBA KECAMATAN SEULIMUM KABUPATEN ACEH BESAR - Chairanisa Anwar; Fauziah Andika; Eva Rosdiana; Soviawati Soviawati (Universitas Ubudiyah Indonesia, 2021)
The United Nations Children's Fund (UNICEF) said as many as 30 thousand infant mortality and 10 thousand deaths of children under five in the world in one year prevented through breastfeeding for 6 months, without giving additional food and drink to the baby so that breast care very important in increasing the production of breast milk. The number of babies in Indonesia who receive exclusive breastfeeding tends to decline because more and more babies under the age of 6 months are given formula milk. According to the Indonesian Health Demographic Survey (IDHS), the coverage of exclusive breastfeeding for infants 0-6 months in 2002 was 40%, in 2007 it fell to 32% and in 2010 it fell again to 27.2%. The cause of a pregnant woman not doing breast care, between others are caused by the following factors lack of information obtained from health workers, fear and laziness, and the availability of time to perform breast care during pregnancy. Breast Care It is very important that complications do not occur when breastfeeding the baby later. So a level of behavior is needed, especially for primigravida mothers, regarding the importance of breast care during pregnancyKeywords: breast care, pregnant women